The emperor's caretaker. 2 - Hiiragi, Ichiha; Shouoto, Aya, 1977- (Square Enix Manga & Books, 2025)
'Linhua, now the caretaker of the five-year-old Emperor Zhiyou, Linhua is navigating a life full of new experiences and constant challenges in the dynamic world of the imperial palace. One day, she stumbles upon a letter that just so happens to contain a heartfelt declaration of love! Who wrote this letter, and who was it intended for? Let the intrigue and speculation begin!"--Back cover.